A proposed carbon tax framework for Malaysia and the challenges of implementation in the COVID-19 economic recovery plan / Izlawanie Muhammad - Muhammad, Izlawanie (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
The years 2020 and 2021 were challenging years for many governments worldwide due to the COVID-19 pandemic. In the aftermath of the global health crisis, the International Monetary Fund strongly recommended that governments in developing countries should not only focus on economic recovery but also ensure environmental sustainability. In response to this suggestion, the Malaysian government announced the introduction of a carbon tax in the 12th Malaysian Plan (2021-2025). However, there was little information on the policy, and the government had not announced the framework. The proposed policy also raised the question of how it would be implemented under the COVID-19 economic recovery plan. This study aimed to propose a framework for implementing the Malaysian carbon tax and explore possible obstacles for the government in implementing the policy. A qualitative research methodology was used, involving document analysis and in-depth interviews. Based on the analysis, a Malaysian carbon tax framework consisting of 10 main components was constructed. In implementing the policy, the government needs strategies to overcome various challenges, including lack of expertise and public resistance. In addition to enhancing the Malaysian carbon tax literature, the findings of this study will serve as a solid foundation for the government to implement a feasible and acceptable carbon tax policy.